Ensuring comfort microclimate in the classrooms under condition of the required air exchange - Kapalo, Peter; Voznyak, Orest; Yurkevych, Yuriy; Myroniuk, Khrystyna; Sukholova, Iryna (Eastern-European Journal of Enterprise Technologies, 2018)
We performed comparative analysis of regulatory documents, which relate to ventilation of school premises and operate in European countries at present. We showed the essential difference of the recommended air exchange values. We assessed sanitary and hygienic conditions formed in classrooms at different efficiency of a ventilation system both by analytical calculations and by subjective monitoring of microclimate of experimental measurements conducted in school classrooms, when every pupil-participant performed an assessment of the internal environment in the form of a questionnaire. We measured carbonic acid gas contents emitted in a room and determined the required ventilation intensity in the evaluated school premises. We compared the multiplication factor of air exchange of the ventilation system determined in this way with the values obtained by analytical calculations carried out in accordance with current legislation and standards, which are active in Europe. We made calculations based on known analytical dependencies. We determined performance of the ventilation system of the classroom based on СО2 concentrations in internal and inflow air at various values of the multiplication factor of air exchange. It made possible to state that we can achieve the optimal microclimate parameters at air exchange of 30 m3/h per person. We presented the results of field studies and analytical calculations in the form of tables and visual graphic dependencies. The proposed research method makes it possible to increase accuracy and reliability of air quality control in classrooms by direct measurement of СО2 concentration in a serviced area of a room. The study results provide an opportunity to improve ventilation systems of school buildings. This creates prerequisites for obtaining a social effect due to an increase in labor and learning efficiency